The crystal structure of bis{tetrakis(n-butyl)(μ-hydroxy)(2,3,5,6-tetrafluorobenzoate) (μ 3-oxo)ditin(IV)} - He Lifang; Li Biao; Hou Xinbo; Wu Xiongwei; Hou Yihu; Zhu Xiaoming; Zhang Fuxing (Zeitschrift für Kristallographie - New Crystal Structures, 2025)
C46H76F8O8Sn4, monoclinic, P21/n (no. 14), a = 13.2408(8) Å, b = 14.3875(9) Å, c = 15.9892(10) Å, β = 104.2490(10)°, V = 2952.3(3) Å3, Z = 2, Rgt (F) = 0.0434, wRref (F 2) = 0.1148, T = 296 (2) K.